2015
DOI: 10.15376/biores.10.3.4826-4842
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Optimized Flow Pattern on Pollutant Removal and Biogas Production Rate Using Wastewater Anaerobic Fermentation

Abstract: This paper introduces a new-type of antigravity mixing method, which was applied in the biogas production process, using organic wastewater fermentation. It was found that the digesters with two designs, a highposition, centralized pressure outlet and a high-position, dispersed pressure outlets, both lead to an increase in biogas production rates by 89% and 125%, respectively. The biogas production peak appeared 1 day and 7 days earlier, and the COD removal rates were raised by 27% and 42%, respectively. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Rajeshwari (2002) pointed out that the firm attachment of the biological matter to the support surfaces also can be critical to the operation. Various researchers have evaluated such systems for the treatment of P&P mill wastewaters (Haggblom and Salkinojasalonen 1991;Rusten et al 1994;Huang et al 2015). Huang et al (2015) fluidized the sludge particles themselves as a relatively uniform mixture.…”
Section: Anaerobic Fluidized Bedmentioning
confidence: 99%
See 1 more Smart Citation
“…Rajeshwari (2002) pointed out that the firm attachment of the biological matter to the support surfaces also can be critical to the operation. Various researchers have evaluated such systems for the treatment of P&P mill wastewaters (Haggblom and Salkinojasalonen 1991;Rusten et al 1994;Huang et al 2015). Huang et al (2015) fluidized the sludge particles themselves as a relatively uniform mixture.…”
Section: Anaerobic Fluidized Bedmentioning
confidence: 99%
“…Various researchers have evaluated such systems for the treatment of P&P mill wastewaters (Haggblom and Salkinojasalonen 1991;Rusten et al 1994;Huang et al 2015). Huang et al (2015) fluidized the sludge particles themselves as a relatively uniform mixture.Unlike aerobic systems, in which aeration serves as a means to mix the liquid by the rise of bubbles, anaerobic systems use mechanical agitation, e.g. an impeller, to provide adequate mixing of liquid.…”
mentioning
confidence: 99%
“…Huang et al designed a slurry recirculation digester for the anaerobic digestion of straw granules. It was found that, although the particle size was less than 3 mm, blockages could easily form [13]. Xiong et al reported that in straw digestion, gas recirculation tends to bring straw particles to the liquid surface and deposits crusts on the liquid surface, which is not conducive to digestion [14].…”
Section: Introductionmentioning
confidence: 99%
“…This pilot scale system is situated near a pig farm in Suining City, Sichuan Province, China, which is located at a latitude of 30 • 15 -30 • 55 N and longitude of 105 • 13 -105 • 48 E. Although a number of anaerobic digester pattern have been proposed, most of the studies involved were focus on pH, initial substrate concentration, and chemical oxygen demand (COD), only a few studies have been explored heat transfer performance and economical digester temperature of anaerobic digestion system. Nevertheless, comparing with general anaerobic digester [13,19], higher heat and mass transfer rates are most significant advantages. Therefore, the biogas production performance and heat transfer performance of the MFD were evaluated with respect to the pilot scale digestion.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the biogas industry calls for more progress in this aspect. With the rapid development of biogas industry, especially the vigorous development of large-scale biogas projects, many countries have replaced traditional household biogas digesters with large-scale biogas projects [9][10][11], which puts forward higher requirements for the design of agitation process [12][13]. The large-scale biogas plants such as Deqingyuan Ecological Farm were constructed, with the annual treatment capacity of 80,000 t of chicken manure and 100,000 t of sewage [14].…”
Section: Introductionmentioning
confidence: 99%